Does radio-opaque contrast improve radiographic localisation of percutaneous central venous lines?. Issue 1 (1st January 2004) - Odd, D E; Page, B; Battin, M R; Harding, J E
Abstract : Background: Percutaneous central venous lines (long lines) are commonly used in neonatal practice. The position of these lines is important, because incorrect placement may be associated with complications. Aims: To determine whether the addition of radio-opaque contrast material improves the localisation of long line tips over plain radiography. Methods: Radiographs taken to identify long line position were identified in two periods; 106 radiographs without contrast taken between October 1999 and August 2000, and 96 radiographs with contrast between September 2001 and July 2002. Two observers independently reviewed each radiograph to identify the position of the line tip. The formal radiology report was recorded as a third observer. Results: The use of contrast increased the proportion of radiographs in which all observers reported they could see the long line tip (53 (55%) v 41 (39%)). It also increased the proportion where they agreed on anatomical position (57 (59%) v 39 (37%)) and there was a higher kappa coefficient for agreement (0.56 v 0.33). Conclusions: The use of contrast while taking radiographs for the localisation of long line position improves the likelihood that an observer can see a long line tip and reduces inter-observer variability. Even using contrast, precise localisation of a long line tip can be difficult.